Solving the phylogeny of toxic dinoflagellates, alexandrium halim (Dinophyceae) - Hii, Kieng Soon. (Universiti Malaysia Sarawak (UNIMAS), 2010)
The genus Alexandrium is a widely distributed dinoflagellate and has the ability to produce potent neurotoxins, saxitoxin (STX) and its deriavatives. In this study, the molecular phylogenetic approach was used to infer the relationships of Alexandrium species distributed worldwide. The clonal cultures of Alexandrium minulllm (AmKBOI, AmKB02, AmKB03, AmKB04, AmKB05 and AmKB06) was used in this study and maintained in SW II medium at 26°C under 12:12 hour light: dark cycle. The total genomic DNA of late exponential phase cultures was extracted and the genomic DNA were used for internal transcribed spacer (ITS) regions amplification and sequencing. Structural analysis of the ITS2 transcript was carried out using the sequences obtained together with related sequences from eighteen species of Alexadrium, Pyrodinium bahamense var. compressum and two outgroup taxa, Coolia malayensis and OSlreopsis lenliclilaris. The results showed conserved four helices secondary structure of ITS2 transcript for all sequences analyzed. Structural comparison between species found a number of compensatory base changes (CBCs). Structural information was then used to perform multiple sequence-structure alignment for phylogenetic anaJy ·s. The phylogenetic inference of Alexandrium species from this study showed nearly similar framework as in the LSU rDNA phylogeny.